The Role of Mitochondrial Dysfunction in Vascular Disease, Tumorigenesis, and Diabetes - Zhunina, Olga A.; Yabbarov, Nikita G.; Grechko, Andrey V.; Starodubova, Antonina V.; Ivanova, Ekaterina; Nikiforov, Nikita G.; Orekhov, Alexander N. (Frontiers in Molecular Biosciences, 2021)
Mitochondrial dysfunction is known to be associated with a wide range of human pathologies, such as cancer, metabolic, and cardiovascular diseases. One of the possible ways of mitochondrial involvement in the cellular damage is excessive production of reactive oxygen and nitrogen species (ROS and RNS) that cannot be effectively neutralized by existing antioxidant systems. In mitochondria, ROS and RNS can contribute to protein and mitochondrial DNA (mtDNA) damage causing failure of enzymatic chains and mutations that can impair mitochondrial function. These processes further lead to abnormal cell signaling, premature cell senescence, initiation of inflammation, and apoptosis. Recent studies have identified numerous mtDNA mutations associated with different human pathologies. Some of them result in imbalanced oxidative phosphorylation, while others affect mitochondrial protein synthesis. In this review, we discuss the role of mtDNA mutations in cancer, diabetes, cardiovascular diseases, and atherosclerosis. We provide a list of currently described mtDNA mutations associated with each pathology and discuss the possible future perspective of the research.